Optimizing effects on airway pressure and minute volume during closed endotracheal suctioning: a simulated lung model. (July 2021) - Jung, Fang; Chou, Shang-Shing P; Yang, Shih-Hsing; Lin, Jau-Chen; Jow, Guey-Mei
A closed suction system is used to remove endotracheal secretions without interrupting the patient's ventilation. Closed suctioning may reduce adverse effects associated with suctioning with, for example, decreased clinical signs of hypoxemia and limited environmental, personnel, and patient contamination. However, it is not clear whether ventilation is maintained during the procedure. We aimed to determine the effects of endotracheal tube (ETT) size, suction catheter (SC) size, and SC length in the ETT on ventilation parameters measured during suction. Suction was performed on a test lung, ventilated with either volume-controlled continuous mandatory ventilation (VC-CMV) or pressure-controlled continuous mandatory ventilation (PC-CMV) using ETT sizes of 6.0–8.5 mm paired with SC sizes of 8–16 French gauge (Fr = 0.33 mm). Airway resistance ( Raw ), peak inspiratory pressure (PIP), positive end-expiratory pressure (PEEP), and expiratory minute volume ( Vexp ) were recorded for each ventilation episode by a HAMILTON- G5 ventilator. Here, Raw was considerably increased by insertion of the SC into the ETT. This Raw effect altered the PIP and Vexp . PIP was increased in VC-CMV because the ventilation area of the ETT was reduced, and Vexp was decreased in PC-CMV in relation to the size of the SC. PEEP decreased with application of the 16 Fr SC and 30 L/min flow rate in VC-CMV. We conclude that airway pressure and minute volume are not maintained during closed endotracheal suctioning with VC-CMV and PC-CMV, respectively. The degree of interference to ventilation is affected through selection of appropriate SC size and ventilation settings.